Lithium manganese iron phosphate positive electrode material prepared by using mixed manganese source and preparation method and application of lithium manganese iron phosphate positive electrode material

By using mixed manganese sources and advanced preparation processes, the discharge ratio and circulation performance of lithium -phosphate iron phosphate iron phosphate iron phosphate iron phosphate iron, and solve the problem of low conductivity and poor circulation performance of existing materials.

CN119370816AActive Publication Date: 2025-01-28JIAOZUO BANLV NANOMATERIALS ENG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411366954.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-28
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have problems such as low discharge specific capacity and poor circulation performance. Especially with the increase in manganese proportion, the conductive properties of the material are significantly reduced.

Method used

The mangible manganese source (mixture of manganese dioxide and manganese acetate) is used to prepare manganese -phosphate iron lithium positive electrode materials, and the uniformity and particle size distribution of the material is improved through the steps such as ultrasound treatment, sand grinding and spray drying.

Benefits of technology

A significant improvement of the discharge ratio and circulation performance of the material, reducing the surface area, reducing the difficulty of the battles processing, and avoiding the problem of reaction between lithium and doping elements to generate other compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370816A_ABST
    Figure CN119370816A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium manganese iron phosphate positive electrode material prepared by using a mixed manganese source and a preparation method and application thereof. The preparation method comprises the following steps: mixing manganese dioxide and manganese acetate to obtain the mixed manganese source; the method comprises the following steps: dispersing a lithium source, a mixed manganese source, an iron source, a phosphorus source and a carbon source in pure water; carrying out sanding treatment; and then carrying out spray drying and calcining to obtain the catalyst. By using the mixed manganese source, on one hand, the specific surface area of the material can be obviously reduced, the processing performance requirement on a battery cell is reduced, and on the other hand, the discharge specific capacity of the material can be obviously increased by mixing the manganese source. The specific surface area of a battery assembled by the obtained lithium manganese iron phosphate positive electrode material is 21.70 m < 2 > / g, the specific discharge capacity is 154.6 mAh / g (0.1 C), 153.7 mAh / g (0.2 C), 150.8 mAh / g (0.5 C) and 148.3 mAh / g (1C), the capacity retention rate of 1C / 20 weeks is 99.41%, and the cycle performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a lithium manganese iron phosphate positive electrode material prepared by using a mixed manganese source, and a preparation method and application thereof. Background Art

[0002] Lithium manganese iron phosphate is a new type of phosphate lithium-ion battery positive electrode material formed by doping a certain proportion of manganese on the basis of lithium iron phosphate. Since manganese and iron are both located in the fourth period subgroup and adjacent in the periodic table, and have similar ionic radius and some chemical properties, doping will not significantly affect the original structure; and through the doping of manganese, the performance advantages of iron and manganese can be effectively combined.

[0003] The theoretical capacity of lithium manganese iron phosphate is the same as that of lithium iron phosphate, which is 170mAh / g. + The electrode potential of / Li is 4.1V, which is much higher than the 3.4V of lithium iron phosphate and is located in the stable electrochemical window of the organic electrolyte system. The high potential of 4.1V makes lithium iron manganese phosphate have the advantage of potential high energy density, which is its biggest advantage over lithium iron phosphate. If the actual capacity of lithium iron manganese phosphate is used to the same extent as lithium iron phosphate, its energy density will be increased by 35% compared with lithium iron phosphate, and compared with lithium manganese oxide with equivalent voltage, its energy density can also be increased by more than 20%. In addition, the raw material cost of lithium iron manganese phosphate is low and environmentally friendly, so the market prospects of batteries and materials are very broad.

[0004] However, as the proportion of manganese increases, the low conductivity makes it difficult to fully utilize the capacity, the electrolyte side reaction makes it difficult to fully utilize the capacity of the material, the charge and discharge capacity is limited, and the introduction of manganese significantly reduces the conductivity of the material. Therefore, it is necessary to provide an improved technical solution for the above-mentioned shortcomings of the prior art. Summary of the invention

[0005] In view of the problems of low discharge specific capacity and poor cycle performance of existing lithium manganese iron phosphate positive electrode materials, the purpose of the present invention is to provide a lithium manganese iron phosphate positive electrode material prepared using a mixed manganese source, and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material using a mixed manganese source, comprising the following steps:

[0008] (1) mixing manganese dioxide and manganese acetate uniformly to obtain a mixed manganese source for later use;

[0009] (2) dispersing the mixed raw materials: lithium source, mixed manganese source, iron source, phosphorus source, and carbon source in pure water by ultrasonic treatment to obtain a slurry for later use;

[0010] (3) sand grinding the slurry;

[0011] (4) spray drying the sand-milled slurry to obtain a precursor powder;

[0012] (5) Calcine the precursor powder to obtain.

[0013] Preferably, in step (1), the molar ratio of manganese dioxide to manganese acetate is (3-1): (1-3);

[0014] In the step (1), a three-stage treatment process is adopted during mixing: first, treatment at 600-800 r / min for 30-40 min, then treatment at 800-1000 r / min for 30-40 min, and finally treatment at 1000-1200 r / min for 30-40 min.

[0015] Preferably, in step (2), the molar ratio of lithium element: manganese element: iron element: phosphorus element in the mixed raw material is 1.03: (0.6-0.5): (0.4-0.5): 1 according to lithium element, manganese element, iron element and phosphorus element;

[0016] In the step (2), the mass of the carbon source in the mixed raw material is 6% of the total mass of the lithium source, the mixed manganese source, the iron source and the phosphorus source.

[0017] Preferably, in step (2), the solid content of the slurry is 30-40%;

[0018] In the step (2), the power of the ultrasonic treatment is 35-40 Hz, the temperature is 25-30° C., and the time is 1-2 h.

[0019] Preferably, in step (2), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium phosphate;

[0020] The iron source is any one or two or more of ferrous phosphate, ferrous oxalate, and ferrous sulfate;

[0021] The phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, iron phosphate, and phosphoric acid.

[0022] Preferably, in step (2), the carbon source is polyvinyl alcohol and polyethylene glycol; the mixing mass ratio of polyvinyl alcohol and polyethylene glycol is 1:1;

[0023] In the step (3), the rotation speed during sand grinding is 800-900 r / min, and the time is 4-6 h; the D50 of the slurry after sand grinding is 200 nm.

[0024] Preferably, in step (4), the discharge temperature during spray drying is 95-110°C;

[0025] In the step (5), the calcination temperature is 660-720° C. and the insulation time is 6-10 hours.

[0026] The present invention provides a lithium iron manganese phosphate positive electrode material, and the lithium iron manganese phosphate positive electrode material is prepared by adopting the preparation method.

[0027] The present invention provides a lithium ion battery, comprising the lithium iron manganese phosphate positive electrode material.

[0028] The present invention provides an application of the lithium iron manganese phosphate positive electrode material in preparing a lithium ion battery.

[0029] Beneficial effects:

[0030] The present invention provides a lithium iron manganese phosphate positive electrode material. By using a mixed manganese source, on the one hand, the specific surface area of ​​the material can be significantly reduced, and the processing performance requirements of the battery core can be reduced. In addition, the mixing of manganese sources can also significantly increase the discharge specific capacity of the material. Compared with the existing method of improving the electrochemical performance of lithium iron manganese phosphate positive electrode materials by doping elements, the method of the present invention has lower cost and can avoid the reaction of lithium with doping elements to generate other compounds that exist on the surface of the material and cannot enter the interior of the structure, thereby causing problems such as insufficient lithium usage in the lithium iron manganese phosphate. The specific surface area of ​​the battery assembled with the lithium iron manganese phosphate positive electrode material obtained by the present invention is 21.70m 2 / g, the discharge specific capacity is up to 154.6mAh / g(0.1C), 153.7mAh / g(0.2C), 150.8mAh / g(0.5C), 148.3mAh / g(1C), the capacity retention rate of 1C / 20 weeks is 99.41%, and the cycle performance is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0032] Figure 1 The charge and discharge curves of the batteries assembled with the lithium iron phosphate positive electrode materials prepared in Example 4, Comparative Example 1 and Comparative Example 2 of the present invention.

[0033] Figure 2 1C cycle result diagram of a battery assembled with the lithium iron phosphate positive electrode material prepared in Example 4 of the present invention.

[0034] Figure 3 This is a SEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0036] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0037] In view of the existing problems, the present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material using a mixed manganese source, comprising the following steps:

[0038] (1) mixing manganese dioxide and manganese acetate uniformly to obtain a mixed manganese source for later use;

[0039] (2) dispersing the mixed raw materials: lithium source, mixed manganese source, iron source, phosphorus source, and carbon source in pure water by ultrasonic treatment to obtain a slurry for later use;

[0040] (3) sand grinding the slurry;

[0041] (4) spray drying the sand-milled slurry to obtain a precursor powder;

[0042] (5) Calcine the precursor powder to obtain.

[0043] Among them, manganese dioxide and manganese tetraoxide are commonly used in manganese-based positive electrode materials; the finished product prepared by manganese dioxide has more stable performance, but it is not conducive to redox when all manganese dioxide is used for calcination, which will cause the problem of low capacity. The present invention uses manganese dioxide and manganese acetate as mixed manganese sources. Since the acetate radical of manganese acetate reacts to generate carbon dioxide during calcination, it has a certain reducibility and takes away oxygen. Therefore, the advantages of high capacity of manganese acetate and low specific surface area of ​​manganese dioxide are combined, and the lithium manganese iron phosphate prepared after mixing has better and excellent performance; and the two are mixed and sanded, because the hardness and particle size of the two materials are different, the particle size distribution of the mixed material will be more reasonable, and it has better capacity performance.

[0044] In a preferred embodiment of the present invention, in step (1), the molar ratio of manganese dioxide to manganese acetate is (3-1): (1-3);

[0045] In a preferred embodiment of the present invention, in step (1), the molar ratio of manganese dioxide to manganese acetate is 1:2;

[0046] In a preferred embodiment of the present invention, in step (1), a high-speed mixer is used for uniform mixing; a three-stage treatment process is adopted during mixing: first, treatment at 600-800 r / min for 30-40 min, then treatment at 800-1000 r / min for 30-40 min, and finally treatment at 1000-1200 r / min for 30-40 min;

[0047] Among them, this method first mixes at a low speed to prevent a certain material from flying away due to being too light, thereby causing insufficient material usage. After mixing at a low speed, it rotates at a high speed to reduce the phenomenon of incorrect ratio.

[0048] In a preferred embodiment of the present invention, in step (2), the molar ratio of lithium element: manganese element: iron element: phosphorus element in the mixed raw material is 1.03: (0.6-0.5): (0.4-0.5): 1 according to lithium element, manganese element, iron element and phosphorus element;

[0049] In a preferred embodiment of the present invention, in step (2), the mass of the carbon source in the mixed raw material is 6% of the total mass of the lithium source, the mixed manganese source, the iron source, and the phosphorus source;

[0050] In a preferred embodiment of the present invention, in step (2), the amount of pure water added is adjusted according to the total mass of the mixed raw materials so that the solid content of the obtained slurry is 30-40%;

[0051] In a preferred embodiment of the present invention, in step (2), the solid content of the slurry is 35%;

[0052] In a preferred embodiment of the present invention, in step (2), the power of ultrasonic treatment is 35-40 Hz, the temperature is 25-30° C., and the time is 1-2 h;

[0053] In a preferred embodiment of the present invention, in step (2), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium phosphate; the iron source is any one or two or more of ferrous phosphate, ferrous oxalate, and ferrous sulfate; the phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, ferrous phosphate, and phosphoric acid;

[0054] In a preferred embodiment of the present invention, in step (2), the carbon source is polyvinyl alcohol and polyethylene glycol; the mixing mass ratio of polyvinyl alcohol and polyethylene glycol is 1:1;

[0055] In a preferred embodiment of the present invention, in step (3), a sand mill is used for sand grinding; the speed of the sand grinding is 800-900 r / min, and the time is 4-6 h; the D50 of the slurry after sand grinding is 200 nm;

[0056] In a preferred embodiment of the present invention, in step (4), the discharge temperature during the spray drying process is 95-110°C;

[0057] In a preferred embodiment of the present invention, in the step (5), calcination is carried out in a graphite sagger in an inert atmosphere; the calcination temperature is 660-720° C., and the holding time is 6-10 h.

[0058] In a preferred embodiment of the present invention, in the step (5), the calcination temperature is 680° C. and the holding time is 9 hours.

[0059] The invention provides a lithium iron manganese phosphate positive electrode material, and the lithium iron manganese phosphate positive electrode material is prepared by adopting the preparation method used.

[0060] The present invention provides a lithium ion battery, comprising the lithium iron manganese phosphate positive electrode material.

[0061] The present invention provides an application of the lithium iron manganese phosphate positive electrode material in preparing a lithium ion battery.

[0062] The following is a detailed description of a lithium manganese iron phosphate positive electrode material prepared by using a mixed manganese source, a preparation method thereof, and an application thereof by means of specific embodiments.

[0063] Example 1

[0064] This embodiment relates to a method for preparing a lithium manganese iron phosphate positive electrode material using a mixed manganese source, comprising the following steps:

[0065] (1) Manganese dioxide and manganese acetate in a molar ratio of 3:1 are placed in a high-speed mixer and treated in three stages: first, at 700 r / min for 30 min, then at 900 r / min for 30 min, and finally at 1100 r / min for 30 min; after being mixed evenly, a mixed manganese source is obtained and set aside;

[0066] (2) dispersing the mixed raw materials: lithium hydroxide, iron phosphate, mixed manganese source, diammonium hydrogen phosphate, and carbon source (the mixing mass ratio of polyvinyl alcohol and polyethylene glycol is 1:1) in pure water through ultrasonic treatment to obtain a slurry for later use;

[0067] Wherein, according to lithium element, manganese element, iron element and phosphorus element, the molar ratio of lithium element: manganese element: iron element: phosphorus element in the mixed raw material is 1.03:0.6:0.4:1;

[0068] The mass of the carbon source in the mixed raw material is 6% of the total mass of the lithium source, the mixed manganese source, the iron source and the phosphorus source;

[0069] The power of ultrasonic treatment was 35 Hz, the temperature was 25°C, and the time was 1 h; the solid content of the obtained slurry was 35%;

[0070] (3) sand grinding the slurry;

[0071] The speed of the sand milling was 800 r / min and the time was 4 h. The D50 of the slurry after sand milling was 200 nm.

[0072] (4) spray drying the sand-milled slurry to obtain a precursor powder;

[0073] The discharge temperature during spray drying was 110°C to reduce the moisture content;

[0074] (5) The dried precursor powder is placed in a graphite sagger and kept at 680° C. for 9 h under an inert atmosphere to obtain a lithium manganese iron phosphate positive electrode material.

[0075] Example 2

[0076] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Embodiment 1 in that the molar ratio of manganese dioxide to manganese acetate in step (1) of this embodiment is 2:1, and the other steps and parameters are the same as those in Embodiment 1.

[0077] Example 3

[0078] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Embodiment 1 in that the molar ratio of manganese dioxide to manganese acetate in step (1) of this embodiment is 1:1, and the other steps and parameters are the same as those in Embodiment 1.

[0079] Example 4

[0080] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Embodiment 1 in that the molar ratio of manganese dioxide to manganese acetate in step (1) of this embodiment is 1:2, and the other steps and parameters are the same as those in Embodiment 1.

[0081] Example 5

[0082] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Embodiment 1 in that the molar ratio of manganese dioxide to manganese acetate in step (1) of this embodiment is 1:3, and the other steps and parameters are the same as those in Embodiment 1.

[0083] Example 6

[0084] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that: in step (2) of this embodiment, the molar ratio of lithium element: manganese element: iron element: phosphorus element is 1.03:0.5:0.5:1, and the other steps and parameters are the same as those in Example 4.

[0085] Example 7

[0086] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that the solid content of the slurry in step (2) of this embodiment is 30%, and the other steps and parameters are the same as those of Example 4.

[0087] Example 8

[0088] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that the solid content of the slurry in step (2) of this embodiment is 40%, and the other steps and parameters are the same as those of Example 4.

[0089] Example 9

[0090] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that polyvinyl alcohol is the only C source in step (2) of this embodiment, and the other steps and parameters are the same as those of Example 4.

[0091] Example 10

[0092] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that in step (2) of this embodiment, polyethylene glycol is the only C source, and the other steps and parameters are the same as those of Example 4.

[0093] Embodiment 11

[0094] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that the calcination condition in step (5) of this embodiment is to keep the temperature at 660° C. for 9 hours, and the other steps and parameters are the same as those in Example 4.

[0095] Example 12

[0096] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that the calcination condition in step (5) of this embodiment is to keep the temperature at 700° C. for 9 hours, and the other steps and parameters are the same as those in Example 4.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that manganese dioxide is used as the only manganese source in step (1) of this example, and the other steps and parameters are the same as those of Example 4.

[0099] Comparative Example 2

[0100] This comparative example provides a method for preparing a lithium manganese iron phosphate positive electrode material, which is different from Example 4 in that manganese acetate is used as the only manganese source in step (1) of this example, and the other steps and parameters are the same as those of Example 4.

[0101] Application Examples

[0102] (1) Preparation of the battery to be tested

[0103] The lithium iron manganese phosphate positive electrode materials prepared in the embodiment and the comparative example were respectively used as raw materials, mixed with conductive graphite and polyvinylidene fluoride in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to form a positive electrode sheet; the battery was assembled in the order of negative electrode shell, lithium sheet, electrolyte, diaphragm, electrolyte, positive electrode sheet and positive electrode shell, and then placed in a manual button battery sealing machine for sealing.

[0104] (2) Electrochemical performance test

[0105] The constant current charge and discharge test is used to evaluate the cycle stability of the sample at different current densities. The test is carried out using a blue electric test system. Under the test conditions of a voltage range of 2.5V-4.2V, the electrochemical performance of 0.1C, 0.2C, 0.5C, and 1C are measured respectively. The discharge specific capacity data are shown in Table 1.

[0106] Among them, the charge and discharge curves of the battery assembled with the materials obtained in Example 4, Comparative Example 1 and Comparative Example 2 under 0.1C are as follows: Figure 1 shown.

[0107] According to the discharge specific capacity of 0.1C-1C, the rate performance data of 0.2C / 0.1C, 0.5C / 0.1C and 1C / 0.1C are calculated, as shown in Table 1.

[0108] Under the test condition of 1C charge and discharge rate, the battery was charged and tested multiple times to determine the cycle performance at 1C. The 1C / 20-week capacity retention rate is shown in Table 1.

[0109] Among them, the 1C cycle results of the battery assembled with the material obtained in Example 4 are as follows: Figure 2 shown.

[0110] (3) Specific surface area determination

[0111] Referring to the standard “GB / T 19587-2017 Determination of specific surface area of ​​solid substances by gas adsorption BET method”, the specific surface area of ​​the lithium manganese iron phosphate positive electrode materials obtained in the examples and comparative examples was measured, and the results are shown in Table 1.

[0112] (4) SEM analysis

[0113] Figure 3 This is a SEM morphology of the lithium iron manganese phosphate positive electrode material prepared in Example 4 of the present invention. As can be seen from the figure, the lithium iron manganese phosphate positive electrode material prepared in Example 4 is a spherical morphology formed by the accumulation of primary particles. The sand grinding process can change the primary particle size of the material. The size of the material is about 15um. The particle size has an important influence on the Li + has a significant impact on transmission.

[0114] Table 1 Performance test results of lithium iron manganese phosphate positive electrode materials prepared in different embodiments and comparative examples

[0115]

[0116] According to the comparison of Examples 1-5, if the molar ratio of manganese dioxide to manganese acetate is adjusted, not only the specific capacity of the material can be changed, but also the specific surface area of ​​the finished product can be controlled, which is convenient for the subsequent preparation of the battery cell and reduces the difficulty of the preparation process.

[0117] According to the comparison of Example 4, Example 7, and Example 8, it can be seen that if the solid content of the slurry is adjusted, the reaction rate of the material in the precursor in the slurry will be affected, and when the solid content is 40%, as the particle size becomes finer and finer, the slurry will expand in volume. In the later stage of sand grinding, the slurry becomes more viscous, which is not conducive to long-term cyclic sand grinding. During the later spraying, the slurry is too thick and it is easy to clump and dry on the atomizing nozzle when passing through the nozzle, clogging the nozzle and causing obvious particles to appear after spraying.

[0118] According to the comparison of Example 4, Example 9 and Example 10, it can be seen that if the type of carbon source is adjusted, both the capacity and the specific surface area will be significantly affected, because when different carbon sources are calcined, the residual mode and content on the surface of the material will be different; after the present invention uses a mixed carbon source, not only a smaller specific surface area can be retained, but also the capacity of the material can reach 154.6 mAh / g.

[0119] According to the comparison of Example 4, Example 11, and Example 12, if the calcination temperature is adjusted, the crystallinity of the finished product will be affected, thereby affecting the capacity and cycle of the material. Too high a temperature may cause the grain size of the material to become larger and the specific surface area to become smaller, which is not conducive to the release and embedding of lithium ions in the material. At the same time, oxygen-deficient compounds may be generated, which promotes secondary recrystallization and has an adverse effect on the electrochemical properties of the material. Therefore, choosing a suitable calcination temperature is crucial to obtaining lithium iron manganese phosphate with good electrochemical properties.

[0120] According to the comparison between Example 4 and Comparative Examples 1-2, if the mixed manganese source is changed to a single manganese source, the calcination of manganese dioxide is not conducive to redox, which will result in a low capacity of the finished product; while when manganese acetate is calcined, gas will be generated due to the decomposition of acetate, forming micropores on the surface of the material, which is conducive to Li +However, when manganese acetate is used as the material, it is easy to form fine powder due to its low hardness, resulting in poor particle size distribution. However, the present invention uses the two materials to be mixed and then sand-milled, and because the hardness of the materials is different, the particle size distribution of the materials is more reasonable, and the capacity performance is good.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium iron manganese phosphate positive electrode material using a mixed manganese source, characterized in that: The following steps are involved: (1) mixing manganese dioxide and manganese acetate uniformly to obtain a mixed manganese source for later use; (2) dispersing the mixed raw materials: lithium source, mixed manganese source, iron source, phosphorus source, and carbon source in pure water by ultrasonic treatment to obtain a slurry for later use; (3) sand grinding the slurry; (4) spray drying the sand-milled slurry to obtain a precursor powder; (5) Calcine the precursor powder to obtain.

2. The preparation method according to claim 1, characterized in that In the step (1), the molar ratio of manganese dioxide to manganese acetate is (3-1): (1-3); In the step (1), a three-stage treatment process is adopted during mixing: first, treatment at 600-800 r / min for 30-40 min, then treatment at 800-1000 r / min for 30-40 min, and finally treatment at 1000-1200 r / min for 30-40 min.

3. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of lithium element: manganese element: iron element: phosphorus element in the mixed raw material is 1.03: (0.6-0.5): (0.4-0.5): 1 according to the lithium element, manganese element, iron element and phosphorus element. In the step (2), the mass of the carbon source in the mixed raw material is 6% of the total mass of the lithium source, the mixed manganese source, the iron source and the phosphorus source.

4. The preparation method according to claim 1, characterized in that: In the step (2), the solid content of the slurry is 30-40%; In the step (2), the power of the ultrasonic treatment is 35-40 Hz, the temperature is 25-30° C., and the time is 1-2 h.

5. The preparation method according to claim 1, characterized in that: In the step (2), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium phosphate; The iron source is any one or two or more of ferrous phosphate, ferrous oxalate, and ferrous sulfate; The phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, iron phosphate, and phosphoric acid.

6. The preparation method according to claim 1, characterized in that: In the step (2), the carbon sources are polyvinyl alcohol and polyethylene glycol; the mixing mass ratio of polyvinyl alcohol and polyethylene glycol is 1:1; In the step (3), the rotation speed during sand grinding is 800-900 r / min, and the time is 4-6 h; the D50 of the slurry after sand grinding is 200 nm.

7. The preparation method according to claim 1, characterized in that: In the step (4), the discharge temperature during the spray drying process is 95-110°C; In the step (5), the calcination temperature is 660-720° C. and the insulation time is 6-10 hours.

8. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium manganese iron phosphate positive electrode material is prepared by the preparation method according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: Comprising the lithium iron manganese phosphate positive electrode material as described in claim 8.

10. Use of the lithium iron manganese phosphate positive electrode material as claimed in claim 8 in the preparation of a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method of spherical lithium manganese iron phosphate with high tap density

    CN115180608A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN117682493A

  • Method for preparing lithium manganese iron phosphate positive electrode material from phosphatization residues

    WO2023236511A1